A Dynamic Mixture Model for Non‐equilibrium Multiphase Fluids. (27th November 2021) - Jiang, Y.; Lan, Y.
Abstract: We present a dynamic mixture model for simulating multiphase fluids with highly dynamic relative motions. The previous mixture models assume that the multiphase fluids are under a local equilibrium condition such that the drift velocity and the phase transport can be computed analytically. By doing so, it avoids solving multiple sets of Navier‐Stokes equations and improves the simulation efficiency and stability. However, due to the local equilibrium assumption, these approaches can only deal with tightly coupled multiphase systems, where the relative speed between phases are assumed stable. In this work we abandon the local equilibrium assumption, and redesign the computation workflow of the mixture model to explicitly track and decouple the velocities of all phases. The phases still share the same pressure, with which we enforce the incompressibility for the mixture. The phase transport is calculated with drift velocities, and we propose a novel correction scheme to handle the transport at fluid boundaries to ensure mass conservation. Compared with previous mixture models, the proposed approach enables the simulation of much more dynamic scenarios with negligible extra overheads. In addition, it allows fluid control techniques to be applied to individual phases to generate locally dynamic and visually interesting effects.